Primary cutaneous anaplastic large-cell lymphoma - case report - Luciana Silveira Rabello de Oliveira; Madeleyne Palhano Nobrega; Maira Gomes Monteiro; Wagner Leite de Almeida (Sociedade Brasileira de Dermatologia, 2013)
Primary cutaneous anaplastic large-cell lymphoma is part of the spectrum of CD30+ lymphoproliferative cutaneous processes, characterized by single or multifocal nodules that ulcerate, are autoregressive and recurrent. Extracutaneous dissemination may occur, especially to regional lymph nodes. Histology shows a diffuse, non-epidermotropic infiltrate , anaplastic large lymphoid cells of immunohistochemistry CD30+, CD4+, EMA-/+, ALK-, CD15- and TIA1-/+. Prognosis is good and does not depend on lymphatic invasion. Radiotherapy, removal of the lesion and/or low-dose methotrexate are the treatments of choice. The present study reports the case of a 57-year-old-woman presenting Primary cutaneous anaplastic large-cell lymphoma with multifocal lesions. The pacient evolved with pulmonary involvement 7 years later. She showed a good response to the treatment with low-dose methotrexate prescribed weekly.